ANALYSIS OF CARRYING CAPACITY OF THE PORONG RIVER CAUSED BY SIDOARJO MUD DISPOSAL - Saputro, Robert Agung; Sisno, Suhardjono; Juwono, Pitojo Tri (Fakultas Teknik UB, 2021)
This study aims to examine the sediment distribution models and the stream sediment distribution due to mud disposal of Porong River. It examines how the sediment distribution models and deposition, the distribution of stream sediment due to mud disposal along with its impacts on the river's capacity, and whether the mud disposal has a harmful impact on the water quality. The data used were based on topographic and Bathymetric data of Porong River, cross-sections of the river, and terrain sediment distribution patterns. The study conducted field and secondary data analysis, hydrological analysis, oceanographic analysis of Mura River and river hydraulic analysis. The study concludes that to maintain its capacity and prevent negative impacts, it is necessary to protect the cliffs and embankments along the segment of the river. To protect the community pond area, overburden and/or river dredging activities along with the segments from the branch to the estuary of the river are needed. Furthermore, it is also necessary to add artificial inputs such as submersible Kribs that are arranged on piles to deal with problems of river sediments in the mouth of Porong River.